2017
DOI: 10.1037/xhp0000296
|View full text |Cite
|
Sign up to set email alerts
|

Using a dichoptic moving window presentation technique to investigate binocular advantages during reading.

Abstract: Reading comes with a clear binocular advantage, expressed in shorter fixation times and fewer regressions in binocular relative to monocular visual presentations. Little is known, however, about whether the cost associated with monocular viewing derives primarily from the encoding of foveal information or in obtaining a preview benefit from upcoming parafoveal text. In the present sentence reading eye tracking experiment, the authors used a novel dichoptic binocular gaze-contingent moving window technique to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 75 publications
4
6
0
Order By: Relevance
“…The proportion of alignment for each fixation population further quantifies the role of the vergence system during the reading of multiline texts. Consistent with see also Blythe et al, 2010;Blythe et al, 2006;Jainta et al, 2015;Juhasz et al, 2006;Kirkby et al, 2010;Kirkby et al, 2013;Nikolova et al, 2015;Nikolova et al, 2017Nikolova et al, , 2018, we observed more aligned than unaligned fixations for intraline reading. However, a higher proportion of fixations were unaligned following a return-sweep saccade at fixation onset.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The proportion of alignment for each fixation population further quantifies the role of the vergence system during the reading of multiline texts. Consistent with see also Blythe et al, 2010;Blythe et al, 2006;Jainta et al, 2015;Juhasz et al, 2006;Kirkby et al, 2010;Kirkby et al, 2013;Nikolova et al, 2015;Nikolova et al, 2017Nikolova et al, , 2018, we observed more aligned than unaligned fixations for intraline reading. However, a higher proportion of fixations were unaligned following a return-sweep saccade at fixation onset.…”
Section: Discussionsupporting
confidence: 90%
“…For unaligned fixations, the majority were uncrossed, and only a small proportion were crossed. This pattern of alignment is comparable with previous research using similar stimulus conditions ( Kirkby et al, 2013;Nikolova et al, 2015;Nikolova et al, 2017Nikolova et al, , 2018Schotter, Blythe et al, 2012). The proportion of fixation alignment for each fixation population can be seen in Figure 2 as a function of line length.…”
Section: The Proportions Of Alignment Prior To and Following A Returnsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, although the vast majority of studies that have examined word frequency effects during reading have employed monocular eye movement recordings, some have recorded binocularly (Jainta, Blythe, & Liversedge, 2014; Jainta, Nikolova, & Liversedge, 2016; Juhasz, Liversedge, White, & Rayner, 2006; Kirkby, Blythe, Drieghe, Benson, & Liversedge, 2013; Kliegl et al, 2006; Nikolova, Jainta, & Liversedge, 2016; Nikolova, Jainta, Blythe, Jones, & Liversedge, 2015). However, none of these studies restricted analyses of word frequency effects to cases for which critical words were skipped or fixated by both eyes (for similar restrictions see Kliegl et al, 2006).…”
mentioning
confidence: 99%
“…Recently, eye‐tracking technology has been used to reveal the advantages of binocular vision in reading. By controlling the presentation of text to each eye, researchers have developed a novel saccade‐contingent display‐change technique for investigating the foveal and parafoveal processing of words during natural reading (Jainta, Blythe, & Liversedge, ; Jainta, Nikolova, & Liversedge, ; Nikolova, Jainta, Blythe, & Liversedge, , ). The integration of visual information across space and time and the contributions of binocular vision to natural reading remain areas of active research (Chen & Vroomen, ; Chen, Zhou, Müller, & Shi, ; Kramer & Yantis, ; Scott‐Samuel & Hess, ; Thunell, van der Zwaag, Ogmen, Plomp, & Herzog, ; Wallace & Scott‐Samuel, ).…”
Section: Potential Educational Benefits Of Applying Findings From Vismentioning
confidence: 99%